Flame-retardant recyclable compressible biodegradable cellulose aerogel as well as preparation method and application thereof

By introducing phosphorus/nitrogen-containing bridged organosiloxane and tetraethyl orthosilicate into the bacterial cellulose aerogel, the crosslinked structure is formed, which improves the flame retardant performance and mechanical properties of the aerogel, solves its insufficient application in the field of radiation refrigeration materials, and achieves efficient heat insulation and compressive resistance.

CN120248413APending Publication Date: 2025-07-04JIANGNAN UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510481664.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Bacterial cellulose aerogels have shortcomings in flame retardant properties, mechanical properties and biodegradability, which limits their application scope in the field of radiation refrigeration materials.

Method used

By adding phosphorus/nitrogen-containing bridged organosiloxane and tetraethyl orthosilicate to the bacterial cellulose dispersion, a crosslinked structure is formed, the flame retardant and mechanical properties of the aerogel are enhanced, and the thermal insulation effect is achieved through the porous structure.

Benefits of technology

The prepared flame retardant cyclic compressible biodegradable cellulose aerogel has efficient radiation refrigeration performance in long-wave areas, good heat insulation and compressive resistance, and is suitable for building thermal management and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248413A_ABST
    Figure CN120248413A_ABST
Patent Text Reader

Abstract

The invention discloses flame-retardant recyclable compressible biodegradable cellulose aerogel and a preparation method and application thereof.The preparation method comprises the following steps that 1, phosphorus / nitrogen-containing bridged organosiloxane and tetraethyl orthosilicate are added into bacterial cellulose dispersion liquid and stirred to be uniform, and a milk white dispersion solution is prepared; (2) heating, curing, pre-freezing and freeze-drying the milky white dispersion solution to obtain the flame-retardant recyclable compressible biodegradable cellulose aerogel, and the phosphorus / nitrogen-containing bridged organosiloxane is prepared by carrying out a reaction on phosphonitrilic chloride trimer and 3-aminopropyltriethoxysilane. The prepared cellulose aerogel is excellent in flame retardance, heat insulation and cyclic compression performance, and has a feasible application prospect in the aspect of radiation refrigeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel materials, and particularly to a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, and a preparation method and application thereof. Background Art

[0002] Thanks to the supercritical drying technology, that is, a method of replacing the liquid in the hydrogel with air while preserving the original continuous three-dimensional structure and the solid network volume, aerogel materials have excellent properties such as low density, high specific surface area, and high porosity, and are widely used in adsorption, catalysis, thermal insulation, electricity, etc. fields, especially in the thermal insulation of walls, pipelines, etc. and building thermal management. At the same time, bacterial cellulose is a kind of nano-scale biopolymer synthesized by specific bacteria, such as microorganisms in the genus Acetobacter and Agrobacterium, during metabolism. It has the characteristics of high purity, ultra-fine network structure, high biocompatibility and degradability, and has rich reserves and wide raw material sources. The prepared bacterial cellulose aerogel inherits and develops these excellent properties to a certain extent, which makes it a hot research topic in the field of functional materials.

[0003] The modification methods of bacterial cellulose aerogels generally endow the aerogels with multifunctionality or improve their application performance by introducing functional groups, surface modifiers or composites with other materials, so as to integrate more flame retardancy, recyclable compression, biodegradability and other properties to meet complex application scenarios. However, few pure bacterial cellulose aerogels can achieve a balance of multiple properties, such as optical efficiency, mechanical properties, environmental compatibility and the feasibility of large-scale preparation, which makes their limitations obvious in specific application scenarios and their application scope is restricted. It is hoped that by reasonably designing the structure and adding functional components, the synergistic enhancement effect of the internal structure and composition of the material can be adjusted to make up for the defects, break through the limitations of existing materials, and improve the overall performance of the material. Summary of the Invention

[0004] Technical Problem

[0005] Bacterial cellulose aerogel is a biomass material with broad application prospects, but it needs to be modified to solve the problems of poor flame retardancy, poor compression resilience and low mechanical properties, and to expand its application scope in different environments in the field of radiative cooling materials.

[0006] Technical Content

[0007] To solve the problems of limited flame retardancy, mechanical properties, biodegradability and application fields of traditional cellulose aerogel fibers, the present invention provides a flame-retardant, recyclable compressible and biodegradable cellulose aerogel, its preparation method and application. The cellulose aerogel prepared by the present invention has excellent flame retardancy, heat insulation and cyclic compression properties, and has a feasible application prospect in radiative cooling.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] The first object of the present invention is to provide a preparation method of a flame-retardant, recyclable compressible and biodegradable cellulose aerogel, comprising the following steps:

[0010] (1) Add a phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate to the bacterial cellulose dispersion, and stir evenly to obtain a milky white dispersion solution;

[0011] (2) Heat and cure the milky white dispersion solution, pre-freeze it, and freeze-dry it to obtain the flame-retardant, recyclable compressible and biodegradable cellulose aerogel;

[0012] The phosphorus / nitrogen bridged organosiloxane is prepared by reacting hexachlorocyclotriphosphazene with 3-aminopropyltriethoxysilane.

[0013] In one embodiment of the present invention, in step (1), the preparation method of the phosphorus / nitrogen bridged organosiloxane is:

[0014] Under a nitrogen atmosphere, mix hexachlorocyclotriphosphazene with 3-aminopropyltriethoxysilane, stir and react at 45-55 °C for 20-30 min, and then raise the temperature to 80-85 °C and continue to react for 3-3.5 h to obtain a clear, transparent and light yellow phosphorus / nitrogen bridged organosiloxane; the product does not need to be further purified.

[0015] In one embodiment of the present invention, the mass ratio of hexachlorocyclotriphosphazene to 3-aminopropyltriethoxysilane is 1:3.5-4.

[0016] In one embodiment of the present invention, in step (1), hexachlorocyclotriphosphazene is first added to the reaction vessel, and after purging the air in the reaction vessel with nitrogen, 3-aminopropyltriethoxysilane is added dropwise at the gas outlet of the vessel; special attention should be paid to the slow addition rate of 3-aminopropyltriethoxysilane at the initial stage of the reaction to ensure good control of the reaction rate and obtain a reaction product with high purity.

[0017] In one embodiment of the present invention, in step (1), after the dropwise addition of 3-aminopropyltriethoxysilane is completed, the initial reaction temperature of the system should not be lower than 20 °C, and it is preferably maintained at 45-55 °C. Otherwise, the reactants are likely to solidify, affecting the reaction process and the purity of the product. Under these conditions, the initial reaction of the system is maintained for 20-30 min, and then the temperature is raised to 80-85 °C until the reaction ends.

[0018] In one embodiment of the present invention, in step (1), the concentration of the bacterial cellulose dispersion is 0.2-0.8 wt%.

[0019] In one embodiment of the present invention, in step (1), the concentration of the bacterial cellulose dispersion is 0.8 wt%.

[0020] In one embodiment of the present invention, in step (1), the mass ratio of the phosphorus / nitrogen bridged organosiloxane to the bacterial cellulose is 0.5-2:1.

[0021] In one embodiment of the present invention, in step (1), the mass ratio of the phosphorus / nitrogen bridged organosiloxane to the bacterial cellulose is 1:1.

[0022] In one embodiment of the present invention, in step (1), the mass ratio of tetraethyl orthosilicate to the bacterial cellulose is 0.1-0.5:1.

[0023] In one embodiment of the present invention, in step (1), the mass ratio of tetraethyl orthosilicate to the bacterial cellulose is 0.3:1.

[0024] In one embodiment of the present invention, in step (1), the phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate need to be added dropwise to the bacterial cellulose dispersion; first, the phosphorus / nitrogen bridged organosiloxane is added dropwise, and then tetraethyl orthosilicate is added after an interval of 15-20 min.

[0025] In one embodiment of the present invention, in step (1), the stirring temperature is 15-22 °C (room temperature), the rotation speed is 1000-1200 rpm, and the stirring time is 40-60 min.

[0026] In one embodiment of the present invention, in step (2), the temperature for heat curing is 55-65 °C, and the time is 15-20 min.

[0027] In one embodiment of the present invention, in step (2), the temperature for pre-freezing is -78 to -6 °C, and the time is 12-36 h.

[0028] In one embodiment of the present invention, in step (2), the temperature for freeze-drying is -76 to -50 °C, and the time is 48-72 h.

[0029] The beneficial technical effects of the present invention are as follows:

[0030] The phosphorus / nitrogen bridged organosiloxane in the present invention contains phosphorus and nitrogen elements, while tetraethyl orthosilicate contains silicon element. The synergistic effect can effectively improve the flame retardant performance of the aerogel material; the phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate hydrolyze in the bacterial cellulose dispersion to generate compounds containing a large number of hydroxyl groups, and a large number of hydroxyl groups in the cellulose molecule form covalent bonds or hydrogen bonds with them, forming crosslinks between cellulose molecules, making the system skeleton stable, thereby improving the compressive performance of the aerogel.

[0031] The phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate in the present invention hydrolyze into polyhydroxy compounds, and then undergo a condensation reaction with cellulose to form Si-O-C covalent bonds, significantly enhancing the rigid connection of the fiber skeleton, inhibiting the irreversible structural collapse caused by the skeleton slippage during the compression of the aerogel, and endowing the material with the characteristics of an "elastic skeleton"; at the same time, the hydrogen bonds formed between molecules undergo reversible breakage and reconnection under the stressed and relaxed states, giving the aerogel a certain elastic recovery ability; in addition, the porous structure of the aerogel can also absorb the initial compressive stress, disperse the local stress concentration, dissipate the residual energy, and optimize the stress transmission path through the bending of the pore walls, relative slippage, and elastic deformation. The multiple effects improve the crosslinking degree of the cellulose network and fill the skeleton gaps, endowing it with good mechanical strength and compression resilience.

[0032] In addition, the thermal decomposition of the phosphorus / nitrogen bridged organosiloxane releases phosphorus free radicals (PO·) and NH3, which dilute oxygen, inhibit the combustion chain reaction, and at the same time promote the dehydration and carbonization of cellulose to form a dense carbon layer; while the SiO2 carbon layer generated by silicon element isolates heat and oxygen to a certain extent, further improving the flame retardant efficiency of the cellulose aerogel.

[0033] The flame retardant, recyclable, compressible and biodegradable cellulose aerogel of the present invention has a relatively stable and high emissivity in the long wave region (6 - 18 μm), which is conducive to the efficient dissipation of the heat of the material itself in the form of thermal radiation; at the same time, in other bands, the low and stable emissivity of the material can reduce the absorption of external heat such as solar radiation. With this "heat dissipation - heat insulation" dual mechanism, the aerogel of the present invention can achieve a more effective radiative cooling effect.

[0034] The flame retardant, recyclable, compressible and biodegradable cellulose aerogel of the present invention has the characteristics of high production efficiency, simple process, good repeatability, and easy batch production. The obtained aerogel material has good flame retardant performance, and at the same time has excellent heat insulation and compressive performance, promoting the application of cellulose aerogel materials as flame retardant materials, heat insulation materials, compressive materials, and radiative cooling and thermal management materials in actual production and life. Description of the Drawings

[0035] Figure 1 Schematic diagram of the three-dimensional model of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention.

[0036] Figure 2 SEM images of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure cellulose aerogel prepared in Comparative Example 3.

[0037] Figure 3 Graph of the change in heat release rate over time of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3.

[0038] Figure 4 Graph of the change in total heat release over time of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3.

[0039] Figure 5 Graph of the thermogravimetric test curve of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3.

[0040] Figure 6 Graph of the relationship between reflectance and wavelength of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention.

[0041] Figure 7 Graph of the relationship between emissivity and wavelength of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention.

[0042] Figure 8 Process diagram of the cyclic compression of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention.

[0043] Figure 9 Infrared thermal imaging diagram of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention on the surface of the hot stage.

[0044] Figure 10 Flow chart of the natural degradation of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention in soil.

[0045] Figure 11 Nuclear magnetic resonance spectrum image of the phosphorus / nitrogen bridged organosiloxane of the present invention, including (a) hydrogen spectrum ( 1 HNMR) and (b) phosphorus spectrum ( 31 P NMR) images. Detailed implementation manners

[0046] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0047] Description of material sources:

[0048] Bacterial cellulose (BC) dispersion: The bacterial cellulose (BC) dispersion was purchased from Guilin Qihong Technology Co., Ltd.; specification: 500 g; property: milky white thick paste; mass fraction: 0.8% wt. Solvent: deionized water; grade: reagent grade; no further purification is required; it is used as a basic raw material in the experiments related to the present invention. Hexachlorocyclotriphosphazene: purchased from Leyan Biotechnology Co., Ltd.; specification: 500 g; property: solid particles; no further purification is required. 3-Aminopropyltriethoxysilane: purchased from Leyan Biotechnology Co., Ltd.; specification: 500 g; property: colorless transparent liquid; purity: 99.83%; no further purification is required. Tetraethyl orthosilicate: purchased from Shanghai Macklin Biochemical Co., Ltd.; specification: T819505-500 ml, property: colorless transparent liquid; purity: 98%; no further purification is required.

[0049] Hexachlorocyclotriphosphazene and 3-aminopropyltriethoxysilane are used for the preparation of phosphorus / nitrogen bridged organosiloxane, and the method is as follows:

[0050] Weigh 4.2 g of hexachlorocyclotriphosphazene and 16.0 g of 3-aminopropyltriethoxysilane, and the molar ratio of the two is 1:6; set up a reaction device and safely connect the three-necked flask to the nitrogen cylinder; set the initial heating temperature to 22 °C, add hexachlorocyclotriphosphazene, turn on the magnetic stirrer, and dropwise add 3-aminopropyltriethoxysilane. After the addition is completed, raise the temperature of the oil bath to 50 °C and react for 30 min; then raise the temperature to 80 °C and react for 3 h. The whole process needs to be carried out under a nitrogen atmosphere; finally, a clear, transparent and light yellow phosphorus / nitrogen bridged organosiloxane is obtained.

[0051] Its nuclear magnetic resonance spectrum image is as Figure 11 shown, including (a) hydrogen spectrum ( 1 1H NMR) and (b) phosphorus spectrum ( 31 31P NMR) images. From (a) the hydrogen spectrum ( 1From the \(^1H\) NMR) image, it can be obtained that the chemical shift \(\delta\approx3.5\ ppm\) (peak 1) corresponds to the methylene hydrogen connected to silicon. The siloxane group in the structural formula causes it to appear in this displacement range, confirming the existence of this structure; the chemical shift \(\delta\approx3.0\ ppm\) (peak 2) conforms to the characteristics of the methylene hydrogen connected to nitrogen, corresponding to the nitrogen-carbon connection part in the structural formula; the chemical shift \(\delta\approx1.0 - 1.5\ ppm\) (peak 3) is the displacement range of the methyl and methylene hydrogens of the alkyl chain, which is consistent with the alkyl chain structure in the structural formula; the chemical shift \(\delta\approx0.5\ ppm\) (peak 4) is the methyl hydrogen connected to silicon at this displacement, which is consistent with the silicon-methyl structure in the structural formula; the chemical shift \(\delta\approx4.0\ ppm\) (peak 5) may be the hydrogen in a special environment near the nitrogen-phosphorus heterocycle, which can assist in confirming the existence of the heterocyclic structure; these feedback information is similar to the chemical environment of the hydrogen atoms in the synthetic raw materials: hexachlorocyclotriphosphazene and 3-aminopropyltriethoxysilane, and has traceability, corroborating the existence of this chemical structure. Additionally, from the (b) phosphorus spectrum ( 31 From the \(^{31}P\) NMR) image, it can be obtained that the single peak that appears indicates that there is only one kind of phosphorus atom in the chemical structure of this self-made flame retardant, which is consistent with the single environment of the phosphorus atom in the structural formula; at the same time, the phosphorus spectrum peak displacement is basically consistent with the displacement range of the nitrogen-phosphorus heterocyclic compound, corroborating the existence of the heterocyclic structure, which is also consistent with the phosphorus-nitrogen heterocyclic structure in one of the synthetic raw materials: hexachlorocyclotriphosphazene, supporting the correctness of this chemical structure. The above information all corroborates the consistency of the chemical shift and group attribution of the material with the chemical structural formula in the figure, and verifies the effectiveness of the self-made material synthesized in this invention.

[0052] Example 1

[0053] A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, comprising the following steps:

[0054] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, mechanically stir (rotation speed 1000 r / min) until a uniform dispersion system is formed, dropwise add 0.8 g of phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.24 g of tetraethyl orthosilicate, and mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0055] (2) Pour the obtained dispersion into a mold, place it in an electrothermal constant temperature blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, the pre-freezing temperature is -16 °C, and the time is 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, the temperature is set at -76 °C, and the time is 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0056] Example 2

[0057] A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, comprising the following steps:

[0058] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.4 wt%), add it to a three-necked flask, mechanically stir (rotation speed 1000 r / min) until a homogeneous dispersion system is formed, dropwise add 0.4 g of a phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.12 g of tetraethyl orthosilicate, mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0059] (2) Pour the obtained dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C and dry for 15 min for curing treatment; pre-freeze the cured dispersion with liquid nitrogen, the pre-freezing temperature is -16 °C and the time is 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, the temperature is set at -76 °C and the time is 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0060] Example 3

[0061] A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, comprising the following steps:

[0062] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.2 wt%), add it to a three-necked flask, mechanically stir (rotation speed 1000 r / min) until a homogeneous dispersion system is formed, dropwise add 0.2 g of a phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.06 g of tetraethyl orthosilicate, mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0063] (2) Pour the obtained dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C and dry for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, the pre-freezing temperature is -16 °C and the time is 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, the temperature is set at -76 °C and the time is 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0064] Example 4

[0065] A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, comprising the following steps:

[0066] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, and mechanically stir (at a rotation speed of 1000 r / min) until a uniform dispersion system is formed. Dropwise add 0.4 g of phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.24 g of tetraethyl orthosilicate. Mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0067] (2) Pour the obtained dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel.

[0068] Example 5

[0069] A preparation method of a flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel, comprising the following steps:

[0070] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, and mechanically stir (at a rotation speed of 1000 r / min) until a uniform dispersion system is formed. Dropwise add 0.8 g of phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.4 g of tetraethyl orthosilicate. Mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0071] (2) Pour the obtained dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel.

[0072] Example 6

[0073] A preparation method of a flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel, comprising the following steps:

[0074] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, and mechanically stir (at a rotation speed of 1000 r / min) until a uniform dispersion system is formed. Dropwise add 1.6 g of phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, and then dropwise add 0.24 g of tetraethyl orthosilicate. Mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0075] (2) Load the obtained dispersion into a mold and place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0076] Example 7

[0077] A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel comprises the following steps:

[0078] (1) Take 100 g of a bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, mechanically stir (rotation speed 1000 r / min) until a uniform dispersion system is formed, dropwise add 0.8 g of a phosphorus / nitrogen bridged organosiloxane, mechanically stir for 20 min, then dropwise add 0.08 g of tetraethyl orthosilicate, and mechanically stir for 40 min until a uniform and stable milky white dispersion is formed;

[0079] (2) Load the obtained dispersion into a mold and place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0080] Comparative Example 1

[0081] A preparation method of a biodegradable cellulose aerogel comprises the following steps:

[0082] (1) Take 100 g of a bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, mechanically stir (rotation speed 1000 r / min) until a uniform dispersion system is formed, dropwise add 0.24 g of a phosphorus / nitrogen bridged organosiloxane, and mechanically stir for 60 min until a uniform and stable milky white dispersion is formed;

[0083] (2) Load the obtained dispersion into a mold and place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel.

[0084] Comparative Example 2

[0085] A preparation method of a biodegradable cellulose aerogel, comprising the following steps:

[0086] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, and mechanically stir (rotation speed 1000 r / min) until a uniform dispersion system is formed. Dropwise add 0.08 g of tetraethyl orthosilicate, and mechanically stir for 60 min until a uniform and stable milky white dispersion is formed;

[0087] (2) Load the obtained dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a flame-retardant, recyclable and compressible biodegradable cellulose aerogel.

[0088] Comparative Example 3

[0089] A preparation method of a biodegradable cellulose aerogel, comprising the following steps:

[0090] (1) Take 100 g of bacterial cellulose (BC) dispersion (0.8 wt%), add it to a three-necked flask, and mechanically stir (rotation speed 1000 r / min) until a uniform dispersion system is formed;

[0091] (2) Load the dispersion into a mold, place it in an electrothermal constant temperature air blast drying oven at 60 °C for drying for 15 min for curing treatment; pre-freeze the cured dispersion in a refrigerator, with the pre-freezing temperature being -16 °C and the time being 24 h; place the pre-frozen sample in a freeze dryer for freeze drying, with the temperature set at -76 °C and the time being 72 h to obtain a pure bacterial cellulose aerogel.

[0092] In order to verify the flame retardancy and heat insulation performance of the aerogel products in the above Examples 1-7 and Comparative Examples 1-3. The axial and radial thermal conductivity coefficients and anisotropy values, and limiting oxygen index of the aerogels in each example and comparative example were measured. The test results are shown in Table 1 below.

[0093] Table 1

[0094]

[0095]

[0096] As can be seen from Table 1 above, in terms of the thermal conductivity, including the axial thermal conductivity and the radial thermal conductivity, Examples 1-7 have relatively excellent effects compared with Comparative Examples 1-3, showing good heat insulation performance; at the same time, in terms of the limiting oxygen index, the improvement effects of Examples 1-7 compared with Comparative Examples 1-3 are considerable, and relatively good flame retardant properties are also shown. In addition, although there are some differences in the thermal conductivity and the limiting oxygen index among Examples 1-7 due to the changes in the mass fraction of bacterial cellulose, the addition ratio of phosphorus / nitrogen bridged organosiloxane, and tetraethyl orthosilicate, generally speaking, compared with the average level and Comparative Examples 1-3, the comparative improvement effects of each example are obvious.

[0097] Figure 1 This is a schematic three-dimensional model diagram of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention. From this model diagram, it can be more intuitively seen that there are a large number of voids inside this aerogel material, indicating that it has a high porosity; on the other hand, it also reflects that the cellulose network in the system has a high degree of crosslinking, a complete skeleton structure, and a relatively stable three-dimensional porous structure, which may have a significant impact on its physical-mechanical properties, thermal properties, etc. In terms of physical-mechanical properties, due to the relatively low proportion of solid substances and the high porosity, the material has a small density; at the same time, the high degree of crosslinking of the system and the complete and stable three-dimensional porous structure can also make the aerogel material have a high modulus; in addition, the multi-stage and multi-porous structure shown in the model enables it to absorb the initial compression stress, disperse the local stress concentration, dissipate the residual energy, and optimize the stress transmission path through the bending of the pore wall, relative slip and elastic deformation, endowing it with good compression resilience.

[0098] Figure 2 This is an SEM image of the flame-retardant, recyclable, compressible and biodegradable cellulose aerogel prepared in Example 1 of the present invention. As can be seen from the figure, the pure bacterial cellulose aerogel presents a relatively loose and continuous fiber network-like microstructure, the connection interface between the fibers is relatively smooth, and the overall structure has a certain regularity. However, for the bacterial cellulose aerogel after adding phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate, its microstructure changes significantly, the fiber network is more intricate, with more irregular intersections and protrusions, and has a multi-stage pore structure. This is very likely due to the cross-linking reaction between the products and cellulose molecules after the hydrolysis of phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate in the bacterial cellulose dispersion. And this multi-stage and multi-porous structure enables the aerogel material to absorb the initial compression stress, disperse the local stress concentration, dissipate the residual energy, and optimize the stress transmission path through the bending of the pore wall, relative slip and elastic deformation, laying a foundation for its good compression resilience performance.

[0099] Figure 3The image shows the variation of the heat release rate over time for the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3. From the figure, it can be seen that compared with the aerogel prepared in Comparative Example 3, the peak heat release rate of the aerogel prepared in Example 1 decreased by 68.7%, from 145.5 kW·m -2 to 45.5 kW·m -2 , indicating that the thermal stability of the aerogel in the example was significantly improved.

[0100] Figure 4 The image shows the variation of the total heat release over time for the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3. From the figure, it can be seen that in the initial stage of combustion (0 - 15 s), the total heat release of Comparative Example 3 increased rapidly, showing a relatively fast heat release rate. In contrast, the heat release of Example 1 increased relatively slowly. This indicates that in the initial stage of combustion, compared with Comparative Example 3, the pyrolysis, combustion process, and heat release in the initial stage of Example 1 were inhibited; as time passed (15 - 75 s), although the heat release rate of Comparative Example 3 was still increasing, the upward trend gradually slowed down. The heat release rate of Example 1 also continued to increase, but the increase amplitude was always lower than that of the BC material. Moreover, the final heat release of Comparative Example 3 was much higher than that of Example 1, which further proves that Example 1 has better flame retardancy or thermal stability.

[0101] Figure 5 The image shows the thermogravimetric test curves of the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention and the pure bacterial cellulose aerogel prepared in Comparative Example 3. From the figure, it can be obtained that at about 800 °C, the weight of the cellulose aerogel prepared in Example 1 remained about 42%, while the weight of the pure cellulose aerogel prepared in Comparative Example 3 was only 20% left. By comparison, it can be concluded that the thermal stability of the cellulose aerogel prepared in Example 1 was significantly improved.

[0102] Figure 6 The image shows the relationship between the reflectivity and wavelength of the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention. From the figure, it can be obtained that in the short-wave region (0 - 2 μm), the aerogel in Comparative Example 3 had a stronger reflection ability for certain wavelengths of light, while Example 1 absorbed or transmitted more of these short-wave light rays; in the medium- and long-wave region (2 - 18 μm), the reflectivity of Example 1 remained at a relatively low level and had small fluctuations, which means it mainly absorbed or transmitted medium- and long-wave light rays. In some scenarios that require heat radiation management, such as the thermal management system of buildings, its characteristics can be used to adjust the absorption and dissipation of heat and maintain a suitable temperature environment.

[0103] Figure 7Image of the relationship between the emissivity and wavelength of the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention. It can be seen from the figure that in the short-wave region (0 - 2 μm), the emissivity of Comparative Example 3 is relatively high in some bands, indicating that Comparative Example 3 has a strong emission ability for thermal radiation of certain wavelengths in the short-wave region, while Example 1 has relatively weak emission of thermal radiation in this region; in the medium-wave region (2 - 6 μm), the thermal radiation emission behavior of Comparative Example 3 in the medium-wave region is relatively complex, while the material of Example 1 is relatively stable; in the long-wave region (6 - 18 μm), the emissivity of Example 1 is relatively stable and at a certain level. It should be noted that the emissivity value of Example 1 can reach about 97% at the highest point, which is beneficial for the material to efficiently dissipate its own heat in the form of thermal radiation; at the same time, in other bands, the low and stable emissivity of the material can reduce the absorption of external heat such as solar radiation. Through this dual mechanism of "heat dissipation - heat insulation", the modified aerogel can achieve a more effective radiative cooling effect.

[0104] Figure 8 Process diagram of the cyclic compression of the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention. The aerogel material is compressed to 50% of its original state. When the external force is removed, it can basically return to its original state within 30 s of the aerogel material, showing good compression resilience. Additionally, when a 500 g weight is placed on it, it also shows good compressive strength, that is, it has a relatively high Young's modulus. This is because the phosphorus / nitrogen-bridged organosiloxane and tetraethyl orthosilicate form crosslinking points between cellulose molecules, endowing the material with the characteristics of an "elastic skeleton"; at the same time, the hydrogen bonds formed between molecules break and reconnect reversibly under the stressed and relaxed states, giving the aerogel a certain elastic recovery ability; in addition, the multi-porous structure of the aerogel can also absorb the initial compression stress, disperse local stress concentration, dissipate residual energy, and optimize the stress transfer path through the bending of the pore walls, relative slip, and elastic deformation. Therefore, the aerogel has good elastic recovery performance. At the same time, the stable crosslinking system and three-dimensional porous structure also make this material have good compressive strength.

[0105] Figure 9 Infrared thermal imaging diagram of the flame-retardant, recyclable, compressible, and biodegradable cellulose aerogel prepared in Example 1 of the present invention on the surface of a hot stage. It can be seen from the figure that the cellulose aerogel prepared in the present invention has good heat insulation performance, which is mainly due to the large number of pores existing inside the material. The high porosity brings good heat insulation performance, making it promising for applications in fields such as building thermal management.

[0106] Figure 10Flow chart of the natural degradation of the flame-retardant recyclable compressible biodegradable cellulose aerogel prepared in Invention Example 1 in soil. It can be seen from the figure that the aerogel prepared in Example 1 can reach a degradation rate of about 80% within 150 days in soil, showing relatively good biodegradability, which is in line with the concepts of environmental protection, greenness, and sustainability.

[0107] The embodiments provided above are not intended to limit the scope covered by the present invention, nor are the described steps intended to limit the order of their execution. Obvious improvements made by those skilled in the art to the present invention in combination with the existing well-known general knowledge also fall within the protection scope defined by the claims of the present invention.

Claims

1. A preparation method of a flame-retardant, recyclable, compressible and biodegradable cellulose aerogel, characterized in that, It includes the following steps: (1) Add phosphorus / nitrogen bridged organosiloxane and tetraethyl orthosilicate to the bacterial cellulose dispersion, stir evenly to obtain a milky white dispersion solution; (2) Heat and cure the milky white dispersion solution, pre-freeze it, and then freeze-dry it to obtain the flame-retardant recyclable compressible biodegradable cellulose aerogel; The phosphorus / nitrogen bridged organosiloxane is prepared by reacting hexachlorocyclotriphosphazene with 3-aminopropyltriethoxysilane.

2. The preparation method according to claim 1, characterized in that, In step (1), the preparation method of the phosphorus / nitrogen bridged organosiloxane is as follows: Under a nitrogen atmosphere, mix hexachlorocyclotriphosphazene with 3-aminopropyltriethoxysilane, stir and react at 45-55 °C for 20-30 min, then raise the temperature to 80-85 °C and continue to react for 3-3.5 h to obtain a clear, transparent and light yellow phosphorus / nitrogen bridged organosiloxane.

3. The preparation method according to claim 2, characterized in that, The mass ratio of hexachlorocyclotriphosphazene to 3-aminopropyltriethoxysilane is 1:3.5-4.

4. The preparation method according to claim 1, wherein, In step (1), the concentration of the bacterial cellulose dispersion is 0.2-0.8 wt%.

5. The preparation method according to claim 1, wherein In step (1), the mass ratio of the phosphorus / nitrogen bridged organosiloxane to the bacterial cellulose is 0.5-2:1; the mass ratio of tetraethyl orthosilicate to the bacterial cellulose is 0.1-0.5:

1.

6. The preparation method according to claim 1, wherein, In step (2), the temperature for heat curing is 55-65 °C and the time is 15-20 min.

7. The preparation method according to claim 1, characterized in that, In step (2), the temperature for pre-freezing is -78 to -6 °C and the time is 12-36 h.

8. The preparation method according to claim 1, wherein In step (2), the temperature for freeze-drying is -76 to -50 °C and the time is 48-72 h.

9. A flame-retardant recyclable compressible biodegradable cellulose aerogel prepared by the preparation method according to any one of claims 1-8.

10. Use of the flame-retardant recyclable compressible biodegradable cellulose aerogel according to claim 9 in heat insulation materials, flame retardant materials or radiative cooling materials.

Citation Information

Cited By

  • Preparation and application of flame-retardant tough bacterial cellulose foam

    CN121873422A

  • Flame-retardant tough heat-insulating cellulose aerogel as well as preparation method and application thereof

    CN122011493A